2013
DOI: 10.3399/bjgp13x663091
|View full text |Cite
|
Sign up to set email alerts
|

Quality-assured screening for diabetic retinopathy delivered in primary care in Ireland: an observational study

Abstract: BackgroundAt present, there is no national population-based retinopathy screening programme for people in Ireland who have diabetes, such as those operating in the UK for over a decade. AimTo evaluate a community-based initiative that utilised existing resources in general practice and community optometry/ophthalmology services to provide screening for diabetic retinopathy. Design and settingCross-sectional study using electronic ophthalmic patient screening records in community optometry clinics in Cork, Irel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
2
11
0
1
Order By: Relevance
“…We found a high proportion of subjects with R1 who are at risk of progression to STDR 27. This highlights the need for screening in China, as in the West where population-based screening for DR has already been prioritised 28 29…”
Section: Discussionmentioning
confidence: 72%
“…We found a high proportion of subjects with R1 who are at risk of progression to STDR 27. This highlights the need for screening in China, as in the West where population-based screening for DR has already been prioritised 28 29…”
Section: Discussionmentioning
confidence: 72%
“…Prior to the introduction of a national diabetic retinal screening programme in 2013, the delivery of diabetic retinopathy screening in Ireland was ad hoc. 29 30 Our counterintuitive finding may reflect a self-selection bias whereby patients who chose to seek out retinopathy screening may also actively manage their diabetes in ways that affect their LEA risk. Alternatively, their GPs may be more vigilant about their diabetes management resulting in more referral for retinopathy screening and less risk of LEA, perhaps by more referrals to podiatry services.…”
Section: Discussionmentioning
confidence: 87%
“…Another barrier to implementation of effective screening is delayed examination by a specialist. In a cross-sectional study in Ireland, 395 of 1542 patients were found to have some level of DR, and 11 had proliferative STDR [96]. Of these, 3 were given specialist appointments that were > 5 months from the original referral date [96].…”
Section: Barriers To Screeningmentioning
confidence: 99%